2012
DOI: 10.3889/mjms.1857-5773.2011.0206
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ocimum Gratissimum</i> Linn Causes Dose Dependent Hepatotoxicity in Streptozotocin-Induced Diabetic Wistar Rats

Abstract: Aim: Hepatoprotective effects of Ethanolic extract Ocimum gratissimum leaves (O. gratissimum) in streptozotocin-induced diabetic rats was studied. Material and Methods:Thirty-six adult rats were assigned into six groups (A, B, C, D, E and F) of six rats each. Group A was the control, while diabetes was induced in groups B, C, D, E and F. Fasting blood glucose was determined and rats with blood glucose concentration >18.0 mmol/L were considered diabetic. Group A (non diabetic control) and F (diabetic control) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…These phytochemicals are known to possess antidiabetic activities [ 25 ] and at least one or more of them were present in the fraction. The data from this study gives credibility to existing reports that OG is valuable in the ethno-therapeutic management of diabetes mellitus [ 12 , 19 , 20 , 22 , 32 ]. Apart from the fact that all five fractions were confirmed to be effective, the n -butanol fraction of OG was revealed to be the most effective, since it had the satisfactory ability to revert diabetic alterations to near normal.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These phytochemicals are known to possess antidiabetic activities [ 25 ] and at least one or more of them were present in the fraction. The data from this study gives credibility to existing reports that OG is valuable in the ethno-therapeutic management of diabetes mellitus [ 12 , 19 , 20 , 22 , 32 ]. Apart from the fact that all five fractions were confirmed to be effective, the n -butanol fraction of OG was revealed to be the most effective, since it had the satisfactory ability to revert diabetic alterations to near normal.…”
Section: Discussionsupporting
confidence: 83%
“…Several other investigators have also reported the non-toxic nature of the leaf extract either to the kidney or the liver [ 12 , 13 , 18 , 34 ]. Nevertheless, some other investigators had contrary reports including Mohammed, et al [ 21 ] who reported LD 50 of OG as 1264.9 mg/kg bw, Onaolapo, et al [ 20 ] who reported 912.3 mg/kg bw oral ethanol extract of OG and Okon, et al who calculated the LD 50 of OG to be 4242.6 mg/kg bw [ 17 ]. However, these differences in the LD 50 may be due to the age of the plant, geographical location, season and time of harvest, which have been reported to affect the phytochemical compositions of plants [ 37 ] and ultimately affect its toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the increment in the activities of SGOT, SGPT, LDH and ALP in serum may also be due to the leakage of these enzymes from the liver cytosol into the blood stream 34 , which gives an indication on the hepatotoxic effect of STZ 35 . On the other hand, treatment of the diabetic rats with ethanolic extracts of plants significantly restored liver marker enzymes level.…”
Section: Discussionmentioning
confidence: 99%